2009
DOI: 10.4134/bkms.2009.46.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Linear Weingarten Hypersurfaces in a Unit Sphere

Abstract: Abstract. In this paper, we have considered linear Weingarten hypersurfaces in a sphere and obtained some rigidity theorems. The purpose of this paper is to give some extension of the results due to Cheng-Yau [3] and Li [7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 9 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…As a natural generalization of hypersurface with constant scalar curvature or with constant mean curvature, linear Weingarten hypersurface has been studied in many places ( [5,8,9,11,13,15,16]). Recall that a hypersurface in a Riemannian space form is said to be linear Weingarten if its normalized scalar curvature R and mean curvature H satisfy R = aH + b for some constants a, b ∈ R. In [13], Li, Suh and Wei proved the first rigidity result for linear Weingarten hypersurface in S n+1 (1) under the assumption that the hypersurface is compact. Later, Shu [15] extended this rigidity result to the case of complete linear Weingarten hypersurface with two distinct principle curvatures in real space forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a natural generalization of hypersurface with constant scalar curvature or with constant mean curvature, linear Weingarten hypersurface has been studied in many places ( [5,8,9,11,13,15,16]). Recall that a hypersurface in a Riemannian space form is said to be linear Weingarten if its normalized scalar curvature R and mean curvature H satisfy R = aH + b for some constants a, b ∈ R. In [13], Li, Suh and Wei proved the first rigidity result for linear Weingarten hypersurface in S n+1 (1) under the assumption that the hypersurface is compact. Later, Shu [15] extended this rigidity result to the case of complete linear Weingarten hypersurface with two distinct principle curvatures in real space forms.…”
Section: Introductionmentioning
confidence: 99%
“…In this note, we generalize the weak maximum principle in [4] to the case of complete linear Weingarten hypersurface in Riemannian space form M n+1 (c) (c = 1, 0, −1), and apply it to estimate the norm of the total umbilicity tensor. Furthermore, we will study the linear Weingarten hypersurface in S n+1 (1) with the aid of this weak maximum principle and extend the rigidity results in Li, Suh, Wei [13] and Shu [15] to the case of complete hypersurface. …”
mentioning
confidence: 98%
“…In particular, they extended the main theorem of [7] for the context of Q n+1 c . Meanwhile, Li, Suh and Wei [12] considered the so-called linear Weingarten hypersurfaces immersed in S n+1 , that is, hypersurfaces of S n+1 whose mean curvature H and normalized scalar curvature R satisfy R = aH +b, for some a, b ∈ R. In this setting, they showed that if M n is a compact linear Weingarten hypersurface with nonnegative sectional curvature immersed in S n+1 such that R = aH + b with (n − 1)a 2 + 4n(b − 1) ≥ 0, then M n is either totally umbilical or isometric to a Clifford torus. More recently, the first, second and fourth authors [6] obtained another characterization result concerning complete linear Weingarten hypersurfaces immersed in Q n+1 c…”
Section: Introduction and Statements Of The Resultsmentioning
confidence: 99%
“…To obtain the second lemma, we can argue as in the proof of either Lemma 2.1 of [12] or Lemma 3.2 of [6]. In what follows, as before, R = 1 n(n−1) i,jR ijij .…”
Section: Key Lemmasmentioning
confidence: 99%
“…Suh and G. Wei [7] introduced the so called linear Weingarten hypersurface in a unit sphere S n+1 (1). We can generalize it to a real space form M n+1 (c), that is, a hypersurface in a real space form M n+1 (c) is called a linear Weingarten hypersurface if the scalar curvature R and the mean curvature H satisfy the linear relation αR + βH + γ = 0, where α, β and γ are constants such that α 2 + β 2 = 0.…”
mentioning
confidence: 99%